Droga . pismo Konfederacji Polski Niepodległej, no. 11, 1980 - Konfederacja Polski Niepodległej, [EIC Leszek Moczulski] (Wydawnictwo Polskie, 1980)
Creation and circulation: Issues no. 12-13 from 1981 prepared for print but not published due to the introduction of the Martial Law, when publication ceased to be publised. Republished underground in 1984